Europe: a Civilian Power? - Telò, Mario. author. aut Link
XX, 292 p.
Keywords: What is the European Union international role and identity becoming after the cold war, September 11th and the transatlantic rift? Is the second global actor challenging the trends towards a 'pax americana'? EUROPE: A CIVILIAN POWER? provides an original account of the features and the external relations of the EU as a civilian power in the making. It addresses the key questions on the new security threat, world emergencies challenging the EU, not only as a peace and democracy stablizer on a continental scale, but also as an actor which shares responsibility for global governance and world order. MARIO TELO provides a comparative analysis of regional cooperation in Europe, Africa, Asia and Latin America and focuses on the interregional relations with the EU. He highlights the international relevance of the current EU constitutionalization process and gives a critical review of the concepts of civilian power, soft power, civilizing power, multilateralism, multipolarism, international fragmentation, empire, hegemonic stability and global legitimacy. Analysis of the best literature on international relations and European integration is completed by MARIO's practical experience as an advisor to the EU institutions and a lecturer in Asia and Americas.